Anatomical and radiographic study of the white-eared opossum (didelphis albiventris) skull - Schimming, Bruno C. [UNESP]; Reiter, Luís Felipe F.; Sandoval, Lívia M.; Filadelpho, André L. [UNESP]; Inamassu, Letícia R.; Mamprim, Maria Jaqueline (FapUNIFESP (SciELO), 2016)
This study was made to investigate the anatomical features of the white-eared opossum skull, by osteology and radiographic anatomy. For this, five animals were used without sexual distinction. The skull was examined by radiographic and macroscopic characteristics. The skulls were then subjected to maceration. The skull was described macroscopically according to standard views, i.e. dorsal and caudal, lateral, ventral, and midsagittal. The skull can be divided into facial (viscerocranium) and cranial (neurocranium) regions. The facial region was elongated and more developed than neurocranium. The supraorbital foramen was absent. The tympanic bulla is not well developed. The zygomatic arch was formed by zygomatic process of the temporal bone, zygomatic process of the maxilla, and temporal process of the zygomatic bone. There was no significant difference between bones found in this study when compared with those described for others mammals. These findings may contribute to the better understanding of the anatomy and biology of the white-eared opossum.
Keywords: Anatomy; Didelphis albiventris; Marsupial; Opossum; Radiography; Skull; White-eared opossum; Wild animals